Impact of organic manures, green leaf manures and micronutrients on natural enemies and energy use efficiency in cotton - CHANNAGOUDA, RUDRAGOUDA F; BABALAD, H B; PATIL, R K (The Indian Journal of Agricultural Sciences, 2017)
The field experiment was carried out at MARS, Dharwad during kharif 2010-11 and 2011-12 to study the impact of organic manures, green leaf manures and micronutrients on natural enemies, sucking pest population, energy use efficiency and energy productivity. Among the nutrient management practices, EC (1/3) + VC (1/3) + gliricidia GLM (1/3) equivalent to RDF recorded significantly higher natural enemies population mainly coccinellids, syrphid maggots, Micromus timidis, chrysoperla and spiders/plant (0.80, 1.05, 0.88, 0.72, 1.30 and 1.28) over RDF +FYM (0.35, 0.44, 0.44, 0.44, 1.13 and 0.53, respectively). The foliar spray of panchagavya @ 5% recorded significantly higher natural enemies population, viz. coccinellid adults, syrphid maggots, Micromus timidis, chrysoperla and spiders/plant (0.67, 0.72, 0.64, 1.27 and 1.04/plant, respectively) over bio-digester @ 20% (0.57, 0.64, 0.57, 1.16 and 0.96, respectively).The combined application of EC (1/3) + VC (1/3) + gliricidia GLM (1/3) equivalent to RDF with foliar spray of panchagavya @ 5% recorded significantly higher natural enemies population mainly coccinellid adults, coccinelid grubs, syrphid maggots, Micromus timidis, chrysoperla and spiders/plant (0.88, 1.13, 0.92, 0.75, 1.34 and 1.32/plant, respectively) as compared to RDF + FYM (0.25, 0.38, 0.36, 0.31, 0.74 and 0.31/plant, respectively). At 90 DAS, RDF + FYM @ 5 t/ha recorded significantly lower aphids and thrips populations (2.73, 1.42 per 3 leaves) over other nutrient management practices. The integrated application of EC (1/3) + VC (1/3) + gliricidia GLM (1/3)equivalent to RDN recorded significantly higher energy use efficiency and energy productivity (2.17 and 0.186 kg/MJ, respectively) over FYM @ 5 t/ha + RDF (2.05 and 0.174 kg/MJ). The combined application of EC (1/3) + VC (1/3) + gliricidia GLM (1/3) equivalent to RDN with foliar spray of panchagavya @ 5% recorded significantly higher energy use efficiency and energy productivity (2.27 and 0.194 kg/MJ, respectively) over RDF + FYM.